A biomechanical study of the recovery in spinal stability of flexion/extension and torsion after the resection of different posterior lumbar structures in a sheep model. (August 2013) - Jia, Haobo; Zhu, Shaowen; Ma, Jianxiong; Wang, Jie; Feng, Rui; Xing, Dan; Yang, Yang; Ma, Baoyi; Chen, Yang; Yu, Jingtao; Ma, Xinlong
Posterior lumbar structures are vital for spinal stability, and many researchers thought that laminectomy and facetectomy would lead to severe spinal instability. However, because living organisms have compensatory repair capacities, their long-term condition after injuries may change over time. To study the changes in the lumbar biomechanical stability of flexion/extension and torsion at different time points after the resection of various posterior structures, as well as to assess the capacity for self-healing, sheep that had undergone laminectomy or facetectomy were used as an experimental animal model. The injured sheep models included three groups: laminectomy only, laminectomy plus left total facetectomy, and laminectomy plus bilateral facetectomy. Eight nonoperative sheep were used as the control group. At 0, 6, 12, 24, and 36 weeks after injury, the lumbar specimens were harvested for biomechanical testing using the Instron 8874 servohydraulic biomechanical testing system. The changes in the injured lumbar spine were also analyzed through radiological examination. The lumbar stability in flexion/extension and torsion was severely decreased after the three types of surgery. After 6 weeks, the flexion/extension mechanical parameters recovered substantially; each parameter had returned to normal levels by 12 weeks and exceeded the intact group by 24 and 36 weeks. Torsional stiffness also recovered gradually over time. All injury groups demonstrated decreased intervertebral space and degeneration or even fusion in the small joints of the surgical segment or in adjacent segments. These results indicate that the body has the ability to repair the mechanical instability to a certain extent.